2020
DOI: 10.1016/j.cmet.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Signals to Glutamatergic Neurons in the Ventromedial Hypothalamus to Suppress Carbohydrate Intake

Abstract: Highlights d Hypothalamic scRNA-seq analyses in Klb-CRE mice identified central targets of FGF21 d FGF21 signals to Vglut2 + neurons to reduce sugar intake and sweet-taste preference d FGF21 signals to VMH neurons to suppress sugar intake d FGF21 markedly enhances glucose sensitivity of b-klotho neurons in the VMH Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 72 publications
4
125
0
Order By: Relevance
“…We demonstrate that FGF21 signaling specifically to glutamatergic, but not GABAergic, neurons is required for the increases in energy expenditure and weight loss associated with low protein diet consumption. A requirement for FGF21 signaling to glutamatergic neurons in the ventromedial hypothalamus (VMH) was also recently demonstrated for its ability to regulate sugar intake 30 . However, in that same study FGF21 signaling to neurons in the VMH was not required for FGF21-mediated protection against weight gain 30 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We demonstrate that FGF21 signaling specifically to glutamatergic, but not GABAergic, neurons is required for the increases in energy expenditure and weight loss associated with low protein diet consumption. A requirement for FGF21 signaling to glutamatergic neurons in the ventromedial hypothalamus (VMH) was also recently demonstrated for its ability to regulate sugar intake 30 . However, in that same study FGF21 signaling to neurons in the VMH was not required for FGF21-mediated protection against weight gain 30 .…”
Section: Discussionmentioning
confidence: 97%
“…A requirement for FGF21 signaling to glutamatergic neurons in the ventromedial hypothalamus (VMH) was also recently demonstrated for its ability to regulate sugar intake 30 . However, in that same study FGF21 signaling to neurons in the VMH was not required for FGF21-mediated protection against weight gain 30 . Thus, together these data suggest that FGF21 regulates sugar consumption and body weight through spatially distinct populations of KLB + glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…FGF21 directly signals adipose tissue to improve insulin sensitivity [ 169 , 170 ], while it signals the CNS to increase energy expenditure and decrease body weight [ 169 , 171 , 172 ] ( Figure 2 ). Recent research demonstrated that FGF21 signaling to glutamatergic neurons lowers carbohydrate intake and non-nutritive sweet-taste preference in mice [ 173 ]. Interestingly, FGF21 signaling to the ventromedial hypothalamus (VMH) is required for its effects on lowering carbohydrate intake but not non-nutritive sweet-taste preference or body weight.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in plasma FGF21 in response to PPARα stimulation has been suggested to be involved in a negative feedback loop to inhibit lipolysis ( 60 ). Hepatic FGF21 is also increased in response to high glucose via activation of Carbohydrate-response element-binding protein (ChREBP) ( 61 ) and FGF21 lowers the preference for glucose intake ( 62 ) by stimulation of glutamatergic neurons in the ventromedial hypothalamus (VMH) ( 63 ). Moreover, FGF21 facilitates glucose ( 64 ), lipid uptake ( 65 ) and adipogenesis in the adipose tissue ( 66 ), which prevent ectopic lipid accumulation in liver and skeletal muscle ( 67 ).…”
Section: Introductionmentioning
confidence: 99%